Ill-Posed and Non-Classical Problems of Mathematical Physics and Analysis: Proceedings of the International Conference, Samarkand, Uzbekistan - Lavrent'ev, Mikhail M; Kabanikhin, Sergey I; Begmatov, Akbar H; Dzhuraev, Tukhtamurad D; Saitoh, Saburou; Yamamoto, Masahiro; Abdinazarov, S; Amonov, B. K; Ashurova, Z. R; Begmatov, Akram H; Cavus, Abdullah; Hamarik, Uno; et al. (Inverse and Ill-Posed Problems Series, 2014)
These proceedings of the international Conference "Ill-Posed and Non-Classical Problems of Mathematical Physics and Analysis", held at the Samarkand State University, Uzbekistan in September 2000 bring together fundamental research articles in the major areas of the numerated fields of analysis and mathematical physics. The book covers the following topics: * theory of ill-posed problems * inverse problems for differential equations * boundary value problems for equations of mixed type * integral geometry * mathematical modelling and numerical methods in natural sciences